DESIGN, SYNTHESIS AND COX1/2 INHIBITORY ACTIVITY OF NEW QUINAZOLINE-5-ONE DERIVATIVES - Aboraia, Ahmed S.; Hara, Mohammed A.; Abdelrahman, Mostafa H.; M. Amin, Mohamed; El-Sabbaghab, Osama I. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A new series of 1-(4-Acetylphenyl)-7,7-dimethyl-3-(substitutedphenyl)-1,2,3,4,7,8-octahydroquinazolin-5(6H)-ones (6-15) were synthesized and tested against COX-1 and COX-2 enzymes. Those compounds exhibited strong interaction at the COX-2 binding site and poor interaction at the COX-1 active site. Subjected to in vitro cyclooxygenase COX-1/COX-2 inhibition assay; most of the compounds especially compounds 6, 7, 12, 13, and 16 exhibited potent anti-inflammatory effects, selective COX-2 inhibition, with half-maximal inhibitor concentration (IC50) values of 0.22–1.42 μM and selectivity index (SI) values of 6.16–14.18 compared with celecoxib (IC50 = 0.05 μM and COX-2 SI: 296), diclofenac (IC50 = 0.8 μM and COX-2 SI: 4.87), and indomethacin (IC50 = 0.49 μM and COX-2 SI: 0.08) as reference drugs. Docking study has been carried out to confirm the binding affinity and selectivity of the most active compound (compound 6) to COX-2 enzyme.